Optimization of Renewable energy penetration in Regional Energy System. (October 2018) - Zhang, Ding; Mu, Shujun; Chan, C.C.; Zhou, George You
Abstract: With the rapid development of economy and increase of energy consumption, China faces a great challenge in the balance of energy supply and demand. In the year of 2016, the carbon dioxide emission of China is the 27.3% of the world, which is the first. So, it is of extremely urgent to improve our energy structure. The integration of renewable energy into the energy system is an alternative path. Thus, it is important to optimize the penetration of renewable energy, i.e. to analyze the behavior of the energy system after integrated renewable energy, then the optimal energy penetration can be obtained consequently. Beijing-Tianjin-Hebei region was taken as an example in this paper. According to the energy supply and demand of Beijing-Tianjin-Hebei region in 2015, based on EnergyPLAN model, first, the energy system model of Beijing-Tianjin-Hebei region was established. Second, the behaviors of the energy system of Beijing-Tianjin-Hebei region at different wind and solar power penetration were analyzed. As a result, the optimal penetration of wind and solar in Beijing-Tianjin-Hebei region was obtained, in this penetration, the energy efficiency is highest in the case of ensuring energy supply. This optimization analysis method of renewable energy penetration is suitable for the region, country and area, is of great guiding significance for the sustainable development of energy in China even the world.